Distinct, shared and complementary: gendered agroecological knowledge in review - Elias, Marlène (CAB International, 2016)
The gendered nature of local agroecological knowledge remains poorly recognized. Gender biases in research and practice result in policies, programmes and interventions that are based on an incomplete understanding of local knowledge systems, and particularly of women's knowledge. This review of over 250 articles, books and chapters explores the complex, culturally specific and dynamic relationship between gender and agroecological knowledge, and underscores the central role both rural men and women play in managing biologically diverse, anthropogenic landscapes. Gender relations and norms, including the gender division of rights and responsibilities spatially, temporally and taskwise critically influence the acquisition and adaptation of local agroecological knowledge. Local knowledge varies across not only genders, but also other axes of social differentiation such as age and ethnicity, which intersect to shape the ways individuals, households and communities interact with their environment. Women and men may have different knowledge about the same or different things, and different ways of organizing and transmitting their knowledge. Although gendered spheres of knowledge are distinct, they are also shared, interwoven and complementary; and are neither fixed nor separable. Understanding local knowledge systems requires recognizing the distinctiveness, overlaps and interdependence of gendered knowledge repertoires. Current socio-economic trends are causing rapid shifts in local agroecological knowledge systems and resource management practices, and interrupting inter-generational knowledge transfers. Recognizing and valuing both women's and men's agroeocological knowledge(s) is crucial to preserve this (adaptive and evolving) body of knowledge, the cultures in which it is embedded and the agroecosystems it contributes to sustaining.